First records of the conifers Majonica and Ortiseia from the German Zechstein (upper Permian) of east Thuringia and west Saxony, Germany. Issue 4 (2nd October 2022) - Kerp, Hans; Bödige, Hendrik; Bomfleur, Benjamin; Schneider, Joerg W.
ABSTRACT: Bulk macerations of a mesoflora from the late Permian Zechsteinmergel of Gera-Trebnitz, east Thuringia, yielded – apart from a number of typical Zechstein taxa – two conifers previously unrecorded from the German Zechstein Basin. These two conifer genera, Ortiseia Florin 1964 and Majonica Clement-Westerhof 1987, were so far only known from northern Italy. The type species of Culmitzschia Ullrich 1964 ( C. florinii Ullrich 1964 ), a broad-leaved conifer from the southern margin of the Zechstein Basin, appears to be a synonym of Ortiseia leonardii Florin 1964, the type species of Ortiseia Florin 1964, the latter name having priority. All bona fide species attributed to Culmitzschia after 1964 differ from Culmitzschia as defined by Ullrich (= Ortiseia ) and are transferred to Ullrichia gen. nov., resulting in the new combinations U. intermedia (Florin 1939) Kerp comb. nov., U. laxifolia (Florin 1939) Kerp comb. nov. and U. mucronata (Florin 1939) Kerp comb. nov.